The Relationship Of PIK R And PIK M Activities And Attitudes Towards Reproductive Health Behaviors In Adolescents In Pulo Lor Jombang - Nur Laila Faizah; Rosa Purwanti; Dewi Pitriawati (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction: PIK-R is a platform for GENRE program activities that are run by and for teens. It offers resources and counseling services related to teen family planning and other related topics. Objectives: Concurrently, PIK-R is an extension of the activities that take place when high school students enroll in college or university. Methods: Statistical tests suitable for the current scale were used to the data in Namely to determine the connection between the dependent and independent variables. Results: Mann-Whitney was the statistical test that was used. Students who participated in PIK-R and PIK-M activities exhibited reproductive health attitudes and premarital sexual conduct, according to the findings of the Mann-Whitney test, which had a p value less than 0.05 (p=0.03). Conclusions: Findings suggest a connection between PIK R and PIK M initiatives and adolescent students' perspectives on reproductive health practices.